The return of Crimean gold: from geopolitical conflict to conflict of laws - Rodríguez Pineau, Elena (CUADERNOS DE DERECHO TRANSNACIONAL, 2024)
In the context of the conflict between Ukraine and the Russian Federation over the Crimean peninsula, the return of artefacts displayed in an exhibition on ‘Crimean gold’ in Amsterdam has led to a long-running dispute in the Dutch courts. The restitution to Ukraine was initially based on the 1970 Unesco Convention to be later justified by the application of a loi de police, issued after the Russian invasion to prevent the dispersal of Ukrainian heritage. Such overriding mandatory rule was applied as such despite being part of the lex causae. The intertwining of international law, national rules of private international law and the use of Sonderanknüpfung doctrine to solve the case shows the complexity of cultural heritage protection cases.